PENGARUH HARGA TERHADAP VOLUME PENJUALAN DI UD. CHANDRA AMANDRAYA - Erna Laia (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
The purpose of this study is to determine the effect of price on sales volume in UD. Chandra Amandraya. The type of research used is a quantitative type of causal nature. The source of the data was from consumers, with the population and sample in this study being as many as 52 respondents. Data collection techniques are research instruments or questionnaires. The data analysis method used is a simple linear regression analysis. The results of this study showed that the calculated value of 6,739>ttabel was 1,676. This study can be concluded that there is an influence of price on sales volume in UD. Chandra Amandraya. The suggestions of this study are (1) To increase sales volume, we recommend UD. Candra needs to give a discount on each product at a relatively high purchase price. (2) It is better to get more consumers, the selling price of the product really needs to be adjusted around other businesses. (3) UD. Candra needs to be able to master consumers to increase the volume.